Fundamental concepts of boundary-layer ingestion propulsion - Lamprakis, Ioannis; Sanders, Drewan S.; Laskaridis, Panagiotis (American Institute of Aeronautics and Astronautics (AIAA), 2025)
This work further develops energy-based far-field methods by introducing Galilean covariance in work–energy relationships of flight. The novelty lies in how decomposition formulations are rederived from integral forms of the governing laws applicable to moving control volumes. It is shown that aerodynamic performance is best evaluated in a reference where the aircraft moves through the atmosphere. The advantages are clearly demonstrated through the formulation of a hypothesis on boundary-layer ingestion (BLI) power savings using a series of simplified flat plate–BLI propulsor configurations. This hypothesis links BLI power savings to the energy content within the boundary layer and the propulsor’s ability to attenuate the ingested boundary layer’s velocity profile. Extensive numerical studies on both laminar and turbulent flows are carried out to test this hypothesis, examining different levels of wake recovery achieved through a body force model propulsor with varying load distributions. Near-perfect wake attenuation is shown to yield maximum power savings, but only for higher-Reynolds-number flows, where the influence of aeropropulsive interference on upstream dissipation is minimal. The flat plate findings are extended to a 2D axisymmetric fuselage representation, where baroclinic losses become significant. A maximum power saving of around 8% is achievable at typical cruise conditions for a single-aisle passenger aircraft.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; Mental health; Aerospace & Aeronautics